Inhibitors of the CD73-adenosinergic checkpoint as promising combinatory agents for conventional and advanced cancer immunotherapy - Kurago, Zoya; Guo, Gang; Shi, Huidong; Bollag, Roni J.; Groves, Michael W.; Byrd, J. Kenneth; Cui, Yan (Frontiers in Immunology, 2023)
The cell surface enzyme CD73 is increasingly appreciated as a pivotal non-redundant immune checkpoint (IC) in addition to PD-1/PD-L1 and CTLA-4. CD73 produces extracellular adenosine (eADO), which not only inhibits antitumor T cell activity via the adenosine receptor (AR) A2AR, but also enhances the immune inhibitory function of cancer-associated fibroblasts and myeloid cells via A2BR. Preclinical studies show that inhibition of the CD73-adenosinergic pathway in experimental models of many solid tumors either as a monotherapy or, more effectively, in combination with PD-1/PD-L1 or CTLA-4 IC blockades, improves antitumor immunity and tumor control. Consequently, approximately 50 ongoing phase I/II clinical trials targeting the CD73-adenosinergic IC are currently listed on https://clinicaltrials.gov. Most of the listed trials employ CD73 inhibitors or anti-CD73 antibodies alone, in combination with A2AR antagonists, and/or with PD-1/PD-L1 blockade. Recent evidence suggests that the distribution of CD73, A2AR and A2BR in tumor microenvironments (TME) is heterogeneous, and this distribution affects CD73-adenosinergic IC function. The new insights have implications for the optimally effective, carefully tailored approaches to therapeutic targeting of this essential IC. In the mini-review, we briefly discuss the cellular and molecular mechanisms of CD73/eADO-mediated immunosuppression during tumor progression and therapy in the spatial context of the TME. We include preclinical data regarding therapeutic CD73-eADO blockade in tumor models as well as available clinical data from completed trials that targeted CD73-adenosinergic IC with or without PD-1/PD-L1 inhibitors, and discuss factors that are potentially important for optimal therapeutic outcomes in cancer patients.